Low rates of antibiotic use among ambulatory patients with coronavirus disease 2019 (COVID-19) - Alison G.C. Smith; Eli Wilber; Paulina A. Rebolledo; Joseph Sharp; Sheetal Kandiah; Daniel S. Graciaa; Russell R. Kempker (Cambridge University Press, 2022)
We assessed the prevalence of antibiotic prescriptions among ambulatory patients tested for coronavirus disease 2019 (COVID-19) in a large public US healthcare system and found a low overall rate of antibiotic prescriptions (6.7%). Only 3.8% of positive severe acute respiratory coronavirus virus 2 (SARS-CoV-2) tests were associated with an antibiotic prescription within 7 days.